Properties of fresh polypropylene fibre reinforced concrete under the influence of pozzolans - Leung, Hau-yan; Balendran, Ramapillai V. (Journal of Civil Engineering and Management, 2003)
This paper summarises experimental results of some fresh concrete tests. Polypropylene fibres were added to the concrete mix to produce fibre reinforced concrete. Pozzolanic materials, including pulverised fly ash and silica fume, were used as partial replacement of cement, and their effects on the fresh fibre concrete were reported. Test results showed that the polypropylene fibre reduced the concrete workability significantly by thixotropic effect and decreased the setting time. Substitution of pozzolans also greatly affected the properties. The presence of fly ash increased the workability and setting time but in the presence of silica fume a reverse trend was observed. Empirical equations were proposed.First Published Online: 26 Jul 2012